PEMBENTUKAN CITRA MEREK (BRAND IMAGE) PT BADR SEBAGAI PERUSAHAAN START UP DIGITAL BERBASIS DAKWAH - Layung Paramesti Martha; Aryanto Pratama (Universitas Pakuan, 2019)
AbstractDigital startup companies are new companies in the field of technology that are being developed. Digital startup companies use technology to innovate, evolve and adapt. PT Badr is one of Indonesia's local digital startup companies located in Depok, which was founded on May 15, 2011. Along with its development, the number of digital startup companies that have arise in Indonesia made PT Badr have competitors who have their own uniqueness so that Badr was required to build The company's Brand Image to the public. The majority of Indonesian people adhere to the religion of Islam, so that with the start-up digital start-up companies such as PT Badr will have selling values and characteristics that are different from other companies and be glimpsed by the public. Researchers are interested in doing this research because Badr is a digital startup company that has a unique concept and carries out preaching as an important activity in the religious life of Muslims. Formation of PT Badr's Brand Image using 3 methods, namely, Feature-based, User-imagenary and advertising. Feature-based that is done by PT Badr that is bonding with consumers so consumers, User-Imagenary conducted by PT Badr is a characteristic of PT Badr's service users that is Muslim and that becomes the value of PT Badr in the eyes of consumers, then the advertisements used by PT Badr only use media social advertising in the form of infographics and posters that have Islamic values that can be the main differentiator of PT Badr.Keyword: Digital startup companies, brand image, preaching.